Schoenberg – Schenker – Bach. A Harmonic, Contrapuntal, Formal Braid - Matthew Arndt (Zeitschrift der Gesellschaft für Musiktheorie)
This article follows on the heels of one by Holly Watkins, who argues that music, “a subsystem of the social system of communication,” can evoke the organic (the bodily and the psychic) not by forming a self-contained unity of parts and whole but through the “internal recursiveness” of musical works, their external “recursiveness vis-à-vis other music,” and – crucially – “the knowingness the music displays toward its own operations.” I adopt the premise that music evokes the organic most vividly not through recursive processes in individual systems but through the as-if intentional integration of such processes in multiple systems, of which I concern myself particularly with the harmonic, contrapuntal, and formal domains (or, more precisely, the motivic). I offer correctives to the organicist theories of Arnold Schoenberg and Heinrich Schenker, which similarly concern these domains, and especially to their reception. And I explore this direction through an analysis of J. S. Bach’s Prelude No. 7 in E-flat major from book 1 of The Well-Tempered Clavier, BWV 852, a singular piece that billows forth like an unfathomable blossom.